2016
DOI: 10.1103/physrevb.94.115143
|View full text |Cite
|
Sign up to set email alerts
|

Driving force for martensitic transformation inNi2Mn1+xSn1x

Abstract: The martensitic transformation in Ni 2 Mn 1+x Sn 1−x alloys has been investigated within ab-initio density functional theory. The experimental trend of a martensitic transition happening beyond x = 0.36 is captured within these calculations. The microscopic considerations leading to this are traced to increased Ni-Mn hybridization which results from the Ni atom experiencing a resultant force along a lattice parameter and moving towards the Mn atoms above a critical concentration.The presence of the lone pair e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For all the systems in the AFM E state, the global minimum lies for c/a1.25 which correspond to the non‐modulated martensite phase. This implies that the AFM E state stabilizes the martensitic phase . The computed lattice parameters for the tetragonal martensite phase are presented in Table .…”
Section: Resultsmentioning
confidence: 98%
“…For all the systems in the AFM E state, the global minimum lies for c/a1.25 which correspond to the non‐modulated martensite phase. This implies that the AFM E state stabilizes the martensitic phase . The computed lattice parameters for the tetragonal martensite phase are presented in Table .…”
Section: Resultsmentioning
confidence: 98%
“…The martensitic crystal structure is tetragonal with Fmmm space group for Ni 2+x Mn 1-x Ga ( Figure 4; a = b = 5.469 Å and c = 6.517 Å Table 2. Structural and magnetic transition temperatures of Ni2Mn1+xIn1-x obtained from DSC 346 317 329 359 390 NCMI2 335 292 312 349 397 has a similar tetragonal martensitic crystal structure (space group Fmmm) as shown in Figure 5 for Ni The ab initio calcuation 40 for Ni 2 Mn 1+x Sn 1-x shows that with increase in Mn2 concentration, the Ni atoms move towards both Mn1 and Mn2. The resultant movement is along a lattice parameter.…”
Section: Martensitic Crystal Structurementioning
confidence: 92%
“…36). The ab initio electronic structure calculations for Ni 2 Mn 1+x Sn 1-x were carried out using the PAW method as implemented in the VASP code within GGA for the exchange correlation functional 40 . A supercell consisting of 5  5  1 primitive cells of the L2 1 crystal structure was considered to calculate the behaviour of excess Mn substitution at Sn sites 41 .…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to these results, a very recent work calculated the relative on-site energies of Ni d states using tight binding model for the Ni 2 Mn 1.5 Sn 0.5 alloy and found that these energies are small. Based on these results, the authors ruled out the possibility of Jahn-Teller distortions [17] and suggested that Ni-Mn hybridization and impact of Sn lone pair is responsible for the MPT. Furthermore, extended X-ray absorption fine-structure (EXAFS) measurements suggest that local structural distortions upon excess Mn doping play a crucial role for the austenite to martensitic phase transition [18].…”
mentioning
confidence: 99%